2021
DOI: 10.1007/s00248-021-01793-w
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of the Microbiome of Pocillopora acuta to Reciprocal Transplantation Within Singapore

Abstract: As corals continue to decline globally, particularly due to climate change, it is vital to understand the extent to which their microbiome may confer an adaptive resilience against environmental stress. Corals that survive on the urban reefs of Singapore are ideal candidates to study the association of scleractinians with their microbiome, which in turn can inform reef conservation and management. In this study, we monitored differences in the microbiome of Pocillopora acuta colonies reciprocally transplanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…Similar to the Symbiodiniaceae communities, coral-associated bacterial communities differed between P. acuta colonies inhabiting mangrove and reef environments. Such difference among sites is consistent with previous studies that have identified highly divergent bacterial communities in P. acuta over small spatial scales ( Wainwright et al, 2019 ; Deignan and McDougald, 2021 ). However, despite the dynamic nature of P. acuta microbiomes over small geographical scales, P. acuta microbiomes appear to remain relatively stable under thermal stress ( Epstein et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the Symbiodiniaceae communities, coral-associated bacterial communities differed between P. acuta colonies inhabiting mangrove and reef environments. Such difference among sites is consistent with previous studies that have identified highly divergent bacterial communities in P. acuta over small spatial scales ( Wainwright et al, 2019 ; Deignan and McDougald, 2021 ). However, despite the dynamic nature of P. acuta microbiomes over small geographical scales, P. acuta microbiomes appear to remain relatively stable under thermal stress ( Epstein et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…Few studies have reported dissolved inorganic nutrient concentrations from the Singapore Strait, and existing time series are relatively short and have lower measurement frequency. Our values are broadly consistent with previous studies (Browne et al, 2015;Chénard et al, 2019;Deignan and McDougald, 2021;Gin et al, 2000), which also noted that nutrient concentrations are typically elevated during the SW monsoon. Our data clearly show that the Singapore Strait undergoes strong and consistent seasonal variation (Fig.…”
Section: Seasonality and Range In Dissolved Nutrient Concentrationssupporting
confidence: 92%
“…Similar associations with stress-tolerant symbionts have been observed in urbanized habitats in Singapore 60 , 61 , as well as in environmentally-variable lagoon environments 62 . Prokaryotic communities also tend to reflect the environment in which the coral resides, where corals in marginal habitats can host divergent mucus-associated bacteria 63 . While some host-symbiont associations in urbanized environments may ultimately be beneficial to the coral host, shifts in prokaryotic communities due to urbanization (i.e.…”
Section: Discussionmentioning
confidence: 99%